Indwelling ureteral stenting negatively impacts sexual function transiently after endourological procedure among adult male and female patients: a prospective cohort study - Kangsaputra, Ferdy Bangun; Budiyono, Nur; Brodjonegoro, Sakti Ronggowardhana (Universa Medicina, 2023)
BackgroundUreteral stents, which are widely used after endourological procedures, cause adverse effects. However, its potential impact on sexual function remains unclear in patients undergoing ureteral stenting. This study aimed to investigate sexual function in adult male and female patients undergoing endourological procedures involving ureteral stent placement. MethodsWe conducted a prospective cohort study in a double tertiary care hospital setting with 103 selected patients (53 male and 50 female). We used a self-administered questionnaire-based survey, namely the Indonesian version of the 5-item International Index of Erectile Function (IIEF-5) for male patients and the Indonesian Female Sexual Function Index (Indonesian FSFI) for female patients at three different times (pre-stenting, four weeks after stenting, and four weeks after stent removal). A paired t-test or Wilcoxon test was used for data analysis. ResultsIn the male group, significant changes were noted in the four IIEF-5 domains and overall IIEF-5 scores at pre-stenting and four weeks after stenting (p =0.000). The female group showed significant differences for all FSFI domains and overall FSFI scores at pre-stenting and four weeks after stenting (p=0.000). Most patients in both groups recovered sexual function four weeks after stent removal, as indicated by insignificant differences in the overall IIEF-5 and FSFI scores at pre-stenting and four weeks after stent removal. ConclusionUreteral stenting led to significant but transient sexual dysfunction in both groups at four weeks after stenting. In this regard, male and female patients need to receive counselling and attention, that they may experience temporal sexual dysfunction at least for 4 weeks.